Long-term neuroprotective effects of allopurinol after moderate perinatal asphyxia: follow-up of two randomised controlled trials. Issue 3 (17th November 2011) - Kaandorp, Joepe J; van Bel, Frank; Veen, Sylvia; Derks, Jan B; Groenendaal, Floris; Rijken, Monique; Roze, Elise; Venema, Monica MA Uniken; Rademaker, Carin MA; Bos, Arend F; Benders, Manon JNL
Abstract : Objective: Free-radical-induced reperfusion injury has been recognised as an important cause of brain tissue damage after birth asphyxia. Allopurinol reduces the formation of free radicals, thereby potentially limiting the amount of hypoxia–reperfusion damage. In this study the long-term outcome of neonatal allopurinol treatment after birth asphyxia was examined. Design: Follow-up of 4 to 8 years of two earlier performed randomised controlled trials. Setting: Leiden University Medical Center, University Medical Center Groningen and University Medical Center Utrecht, The Netherlands. Patients: Fifty-four term infants were included when suffering from moderate-to-severe birth asphyxia in two previously performed trials. Intervention: Infants either received 40 mg/kg allopurinol (with an interval of 12 h) starting within 4 h after birth or served as controls. Main outcome measures: Children, who survived, were assessed with the Wechsler Preschool and Primary Scales of Intelligence test or Wechsler Intelligence Scale for Children and underwent a neurological examination. The effect of allopurinol on severe adverse outcome (defined as mortality or severe disability at the age of 4–8 years) was examined in the total group of asphyxiated infants and in a predefined subgroup of moderately asphyxiated infants (based on the amplitude integrated electroencephalogram). Results: The mean age during follow-up (n=23) was 5 years and 5 months (SD 1 year and 2 months). There were no differences in long-term outcome between the allopurinol-treated infants and controls. However, subgroup analysis of the moderately asphyxiated group showed significantly less severe adverse outcome in the allopurinol-treated infants compared with controls (25% vs 65%; RR 0.40, 95%CI 0.17 to 0.94). Conclusions: The reported data may suggest a (neuro)protective effect of neonatal allopurinol treatment in moderately asphyxiated infants.